UN ALBUM MONUMENTAL - FLOAREA, Mihai (BIBLIOPOLIS, 2020)
The monography Românii din jurul României by Vasile Șoimaru – highlights the significant aspects of ethnolinguistic continuity and offers indisputable testimonies of Romanian presence in the South and Central Europe. The theme is not only patriotic but also important economically, politically and strategically. A further ignoration of our roots, the expression of insatisfaction, waiting for solutions – all these can no longer be considered actual. The cult and brave man, Vasile Soimaru, is an example. He forces us to get out of passivity, to abandon our confort and to assume qualitative leaps. Reading this volume, we can conclude that the Romanian nation is on the way to regain self-awareness.